Optimizing Educational Institutions: Web-Based Document Management - Hanif Triyana, Muhammad; Indah Fianty, Melissa (Publisher Cv. Inara, 2023)
Documents, which consist of written or printed materials, play a crucial role in educational activities. Private schools in Tangerang still face challenges in efficiently storing, accessing, and managing educational documents. Manual document storage consumes a significant amount of time and physical space. Therefore, a technology-based solution is required to address this issue. This research aims to develop a web-based Document Management System (DMS) that allows teachers and school staff to easily manage, store, and access educational documents digitally. The software development method employed is the Waterfall model, involving a series of stages ranging from needs analysis to testing and implementation. The outcome is a web based DMS application accessible to teachers in the school. This application enables teachers to view, upload, edit, and download teaching materials effortlessly. Additionally, teachers can manage their teaching schedules and user access rights. The usability of DMS has been tested through User Acceptance Testing (UAT), and users have provided positive feedback on the application. This web based DMS effectively addresses the issues related to document storage in schools, enhancing the efficient management of educational documents, reducing dependence on physical documents, and increasing productivity in the learning process. Consequently, this DMS holds great potential as a valuable tool in the educational context of the school.